Effect of Vermicompost and Liquid Organic Fertilizer on Growth and Yield of Shallot (Allium ascalonicum L.) from True Shallot Seed - Syatrianty Andi Syaiful; Elkawakib Syam’un; Irma Jamaluddin; Fathurrahman (Hasanuddin University, 2026)
This study evaluated the effect of vermicompost and liquid organic fertilizer (LOF) on the growth and yield of shallot (Allium ascalonicum L.) cultivated from true shallot seed (TSS). The experiment was conducted from October 2023 to February 2024 at the Teaching Farm of the Faculty of Agriculture, Hasanuddin University, Makassar, Indonesia. The study used a factorial experiment arranged in a randomized complete block design with two factors. The first factor was vermicompost dosage consisting of 0, 7.5, and 15 t ha⁻¹, while the second factor was LOF concentration consisting of 0, 2.5, 5, and 7.5 mL L⁻¹. The results showed that vermicompost significantly affected several growth and yield parameters. The highest vermicompost dosage (15 t ha⁻¹) produced the highest fresh shoot weight (27.24 g), dry shoot weight (14.89 g), dry bulb weight (13.47 g), yield per plot (0.95 kg m⁻²), and yield per hectare (9.49 t ha⁻¹). Liquid organic fertilizer also significantly improved shallot growth and production. The highest LOF concentration (7.5 mL L⁻¹) resulted in the highest fresh shoot weight (28.17 g), dry shoot weight (15.60 g), dry bulb weight (14.13 g), bulb diameter (27.67 mm), yield per plot (1.00 kg m⁻²), and yield per hectare (9.97 t ha⁻¹). No significant interaction was observed between vermicompost and LOF. The results indicate that both vermicompost and LOF independently enhance the growth and productivity of shallots cultivated from true shallot seed.